Family Meal Practices and Well-Being in Hong Kong: The Mediating Effect of Family Communication. (November 2018) - Ho, Henry C. Y.; Mui, Moses; Wan, Alice; Yew, Carol; Lam, Tai Hing; Chan, Sophia S.; Stewart, Sunita M.
The literature has provided substantial evidence for the positive associations between family meals and well-being. The underlying mechanism of this relationship has not been explicitly examined. The Happy Family Kitchen II project was a cluster randomized controlled trial of a community-based family intervention. Using data from this project, this article examined the direct and indirect associations among family meal practices, family communication time and quality, and well-being in Hong Kong. A total of 1, 261 participants completed a self-administered questionnaire at baseline, 4 weeks, and 12 weeks. Cross-sectional and prospective mediation analyses showed that family meal and family meal preparation indirectly influenced family health, happiness and harmony, subjective happiness, and mental and physical quality of life through their effects on family communication quality. In contrast, family communication time was a weaker mediator of these effects. These findings highlight the role of quality rather than quantity of family communication in promoting well-being.